10.0k views
4 votes
Solve 4(−x + 4) = 12, justifying each step with an algebraic property.

User Scaraveos
by
5.8k points

2 Answers

5 votes
4(-x+4)=12 (You have to use distribution first)
-4x+16=12 (Then, you subtract 16 from both sides)
-4x=-4 (Finally, you have to divide the -4 that's besides x by both sides)
x=1

User LaVache
by
6.2k points
4 votes
4(-x + 4) = 12

Follow PEMDAS. In this case, because you cannot add -x and 4 (x being a variable (changeable number), you distribute 4 to both -x and 4

4(-x) = -4x
4(4) = 16

-4x + 16 = 12

Because of the equal sign, what you do to one side you do to the other.

Isolate the x, subtract 16 from both sides

-4x + 16 (-16) = 12 (-16)

-4x = 12 - 16

-4x = -4

Isolate the x, divide - 4 from both sides

-4x/-4 = -4/-4

x = -4/-4

x = 1

1 is your answer.

hope this helps
User Pham Hoan
by
5.4k points